PENGARUH CORE SELF-EVALUATIONS TERHADAP JOB SATISFACTION DENGAN MEDIATOR CAREER COMMITMENT PADA KARYAWAN PT SINAR SOSRO DI TANGERANG - Ananda Putra Nainggolan; Christine Winstinindah Sandroto (Prosiding Working Papers Series In Management, 2017)
This study was conducted with the aim to determine whether the influence of core self-evaluations on job satisfaction is mediated by career commitment at PT Sinar Sosro employees. Sampling method used is convenience sampling by using sampling of 100 employees of PT Sinar Sosro. Data analysis method used in this research is path analysis method and using multiple regression analysis. Results of data processing using spss 22.0. The results of this study indicate that the influence of core self-evaluations on job satisfaction is mediated by career commitment at PT Sinar Sosro employees. Core self-evaluations have an influence on career commitment. Career commitment can be affect job satisfaction. Core self-evaluations have a significant effect on job satisfaction. Keywords: Core Self-evaluations, Career Commitment, and Job Satisfaction